The role of partners’ educational attainment in the association between HIV and education amongst women in seven sub-Saharan African countries - Harling, Guy; Bärnighausen, Till (Journal of the International AIDS Society, 2016)
Introduction : Individuals’ educational attainment has long been considered as a risk factor for HIV. However, little attention has been paid to the association between partner educational attainment and HIV infection. Methods : We conducted cross-sectional analysis of young women (aged 15-34) in 14 Demographic and Health Surveys from seven sub-Saharan Africa (SSA) countries with generalized HIV epidemics. We measured the degree of similarity in educational attainment (partner homophily) in 75,373 partnerships and evaluated the correlation between homophily and female HIV prevalence at the survey cluster level. We then used logistic regression to assess whether own and partner educational attainment was associated with HIV serostatus amongst 38,791 women. Results : Educational attainment was positively correlated within partnerships in both urban and rural areas of every survey (Newman assortativity coefficients between 0.09 and 0.44), but this correlation was not ecologically associated with HIV prevalence. At the individual level, larger absolute differences between own and partner educational attainment were associated with significantly higher HIV prevalence amongst women. This association was heterogeneous across countries, but not between survey waves. In contrast to other women, for those aged 25-34 who had secondary or higher education, a more-educated partner was associated with lower HIV prevalence. Conclusions : HIV prevalence amongst women in SSA is associated not only with one’s own education but also with that of one’s partner. These findings highlight the importance of understanding how partners place individuals at risk of infection and suggest that HIV prevention efforts may benefit from considering partner characteristics. Keywords: sub-Saharan Africa; education; sexual partnerships; homophily; HIV; partner characteristics.